2016
DOI: 10.1111/inr.12234
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of caring for dying patients in emergency room

Abstract: Findings of the study influence nursing policies toward enhancing education of nurses regarding palliative and end-of-life care in emergency settings. These findings can also influence the value of caring-healing environments for critical and dying patients and their families. Policies can focus on practice and education of families particularly about end-of-life care for critical and dying patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 20 publications
0
30
0
6
Order By: Relevance
“…This was the most common theme to emerge (Bailey et al, 2011b, Bailey et al, 2011c, Grudzen et al, 2011, Wolf et al, 2015, Kongsuwan et al, 2016, Smith et al, 2009, Decker et al, 2015, Chan, 2011, Weil et al, 2015, Marck et al, 2014. Patients are seen as 'living' and the focus is on preserving life, until life ends, therefore there is no period of time where a patient is said to be 'dying' (Bailey et al, 2011c) .…”
Section: Staff Perceive That the Focus Of Care In The Emergency Deparmentioning
confidence: 99%
See 4 more Smart Citations
“…This was the most common theme to emerge (Bailey et al, 2011b, Bailey et al, 2011c, Grudzen et al, 2011, Wolf et al, 2015, Kongsuwan et al, 2016, Smith et al, 2009, Decker et al, 2015, Chan, 2011, Weil et al, 2015, Marck et al, 2014. Patients are seen as 'living' and the focus is on preserving life, until life ends, therefore there is no period of time where a patient is said to be 'dying' (Bailey et al, 2011c) .…”
Section: Staff Perceive That the Focus Of Care In The Emergency Deparmentioning
confidence: 99%
“…In a further paper (Bailey et al, 2011c) found that staff felt that the Emergency Department was not appropriate for end of life care and that death was seen as out of place, with the dead body almost seen as taboo, to be hidden away, staff perceiving the body itself to be a physical sign of failure. Failure in the context of Emergency Department death is mentioned by Marck et al (2014) and Kongsuwan et al (2016). One nurse participant is quoted as saying that 'palliative care in the Emergency Department is focusing on saving life' (Kongsuwan et al, 2016), thus denying the possibility of death being seen as a natural part of life.…”
Section: Staff Perceive That Death Is a Failurementioning
confidence: 99%
See 3 more Smart Citations